Deciphering the poisoning effect of sulfate on a perovskite-derived IrOxHy catalyst for water oxidation in acid - Seow, Justin Zhu Yeow (2023)
A highly efficient and stable oxygen evolution reaction (OER) plays a key role in the commercialization of proton exchange membrane (PEM) water electrolyzers. Perovskite-derived IrOxHy catalysts have been demonstrated to be highly catalytically active in a harsh acidic environment. On the other hand, the inevitable degradation of the PEM can induce the release of sulfate ions, which could poison electrocatalysts. Herein, the poisoning effects of sulfate ions on a representative SrCo0.9Ir0.1O3-δ-derived IrOx Hy catalyst and a standard IrO2 are studied. It is found that, besides sulfate ion adsorption on Ir active sites impacting both Ir-based catalysts, SrSO4 precipitation is the most prominent cause of activity degradation of IrOxHy. This phenomenon is unique to a reconstructed surface undergoing continuous cation leaching from the perovskite-oxyhydroxide interface, in which SrSO4 precipitate blocks electrolyte-accessible IrOxHy-walled channels, preventing further Sr and Co ion leaching from the interface and dehydrating the isolated portion of the blocked channels, resulting in a reduction in the number of Ir active sites and causing the catalyst to have an OER performance stability inferior to commercial IrO2